A universal strategy for high-yield producing water compatible boron nitride nanosheets. (11th November 2020) - Liu, Panlin; Ding, Jiheng; Su, Shengpei; Yu, Hiabin
Abstract : Boron nitride nanosheets (BNNS) have shown great potential in thermal management applications owing to their high thermal conductivity, electrical insulation, and chemical stability. Abstract : Boron nitride nanosheets (BNNS) have shown great potential in thermal management applications owing to their high thermal conductivity, electrical insulation, and chemical stability. To fully realize their extraordinary properties, the preparation and dispersibility of few-layer BNNS should be efficiently addressed. Herein, we developed a facile and efficient one-step mechanochemical exfoliation approach to simultaneously exfoliate and functionalize BNNS in furfuryl alcohol (FA) liquids. Such an exfoliation process led to a high actual yield of 100% and extremely high concentrations, of up to 40 mg g −1 . Furthermore, the bioinspired BNNS freestanding films with nacre-like nanostructures and uniform in-plane orientation were well prepared via a layer-by-layer vacuum filtration process. The resultant bioinspired films showed highly anisotropic thermal conductivities, reaching 48.5 W m −1 K −1 in the in-plane direction and 2.1 W m −1 K −1 in the through-plane direction, respectively. This indicates that our bioinspired films will be promising candidates for thermal management materials for application in electronic devices. In addition, this exfoliating strategy has been confirmed to be a universal approach to efficient, green, and low cost materials and is scalable to produce other 2D materials including graphene, MoS2, etc.